Predicting the output dimensions, porosity and elastic modulus of additive manufactured biomaterial structures targeting orthopedic implants - Bartolomeu, F. (2019)
SLM accuracy for fabricating porous materials is a noteworthy hindrance when aiming to obtain biomaterial cellular structures owing precise geometry, porosity, open-cells dimension and mechanical properties as outcomes. This study provides a comprehensive characterization of seventeen biomaterial Ti6Al4V-based structures in which experimental and numerical investigations (compression stress-strain tests) were carried out. Monomaterial Ti6Al4V cellular structures and multi-material Ti6Al4V-PEEK cellular structures were designed, produced by SLM and characterized targeting orthopedic implants. In this work, the differences between the CAD design and the as-produced Ti6Al4V-based structures were obtained from image analysis and were used to develop predictive models. The results showed that dimensional deviations inherent to SLM fabrication are systematically found for different dimensional ranges. The present study proposes several mathematical models, having high coefficients of determination, that estimate the real dimensions, porosity and elastic modulus of Ti6Al4V-based cellular structures as function of the CAD model. Moreover, numerical analysis was performed to estimate the octahedral shear strain for correlating with bone mechanostat theory limits. The developed models can help engineers to design and obtain near-net shape SLM biomaterials matching the desired geometry, opencells dimensions, porosity and elastic modulus. The obtained results show that by using these AM structures design it is possible to fabricate components exhibiting a strain and elastic modulus that complies with that of bone, thus being suitable for orthopedic implants.